Strategic Planning dan Balanced Scorecard serta Penerapannya pada Restoran Cepat Saji Wendy’s - - Felisia (Jurnal Akuntansi, 2018)
Organizations need to improve their performances in order to compete in global market. To improve performance, organizations need strategies and performance evaluation measurements. Strategies must be allied within the industry which the organizations competed in. Strategies are formulated by evaluating external factors such as opportunities and threats, and internal factors such as strengths and weaknesses. After determining strategies, organizations formulate strategic planning to implement the strategies determined. Organizations also design strategy maps and balanced scorecards to describe how they could create value by connecting their strategic objectives. Fast food industries have grown in the past years. According to QSR Magazine in 2012, Wendy’s is one of the top ten highest rated food chains, next to McDonalds, Kentucky Fried Chicken, Burger King, Pizza Hut, Subway, Dominos Pizza, Strabucks, Dunkin Donuts,andDairy Queen. This article analyzes strategies, strategy map, and balanced scorecard in Wendy’s. Through this article, readers will know the importance of strategic planning, strategy map, and balanced scorecard for organizations.  Keywords: Strategic Planning, Strategy Map, Balanced Scorecard